2010
DOI: 10.1016/j.neuroimage.2010.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Joint analysis of structural and perfusion MRI for cognitive assessment and classification of Alzheimer's disease and normal aging

Abstract: Structural magnetic resonance imaging (MRI) of brain tissue loss and physiological imaging of regional cerebral blood flow (rCBF) can provide complimentary information for the characterization of brain disorders, such as Alzheimer’s disease (AD) but studies into gains in classification power for AD using these image modalities jointly have been limited. Our aim in this study was to determine the joint contribution of structural and perfusion-weighted imaging for the classification of AD in a cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 88 publications
4
32
0
Order By: Relevance
“…Perfusion MR imaging is attractive because disease-specific regional cerebral blood flow information currently obtained with SPECT or FDG PET can be obtained noninvasively with arterial spin labeling in an integrated examination that includes other MR imaging-based modalities (Fig 8). This is an active area of research, and it remains to be seen if perfusion MR imaging can achieve the same diagnostic sensitivity and specificity that has already been demonstrated with FDG PET (177)(178)(179).…”
Section: Perfusion Imagingmentioning
confidence: 95%
“…Perfusion MR imaging is attractive because disease-specific regional cerebral blood flow information currently obtained with SPECT or FDG PET can be obtained noninvasively with arterial spin labeling in an integrated examination that includes other MR imaging-based modalities (Fig 8). This is an active area of research, and it remains to be seen if perfusion MR imaging can achieve the same diagnostic sensitivity and specificity that has already been demonstrated with FDG PET (177)(178)(179).…”
Section: Perfusion Imagingmentioning
confidence: 95%
“…Using an integrated multimodality MRI framework, the UCSF group studied the extent to which cortical thinning and reduced regional cerebral blood flow (rCBF) explain individually or together variability in dementia severity [159, 160]. This study showed that cortical thinning dominated the classification of AD and controls compared to contributions from rCBF.…”
Section: Accomplishments Of the Adni Mri Core To Datementioning
confidence: 99%
“…Cerebral blood flow is a useful surrogate marker of neuronal activity and is a parameter of primary interest in the diagnosis of a variety of diseases including cerebrovascular disease (Conijn et al, 2012) and stroke (Brumm et al, 2010), epilepsy (Nelissen et al, 2006), brain tumors (Koh et al, 2006) and neurodegenerative diseases (Tosun et al, 2010). In addition, cerebral blood flow is an important covariate in all studies of brain function involving the intravenous injection of a tracer, since the transfer of tracer from arterial blood to tissue depends on the regional cerebral blood flow (rCBF).…”
Section: Introductionmentioning
confidence: 99%